2008
DOI: 10.1016/j.chom.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Liver Autoimmunity Triggered by Microbial Activation of Natural Killer T Cells

Abstract: SummaryHumans with primary biliary cirrhosis (PBC), a disease characterized by the destruction of small bile ducts, exhibit signature autoantibodies against mitochondrial Pyruvate Dehydrogenase Complex E2 (PDC-E2) that crossreact onto the homologous enzyme of Novosphingobium aromaticivorans, an ubiquitous alphaproteobacterium. Here, we show that infection of mice with N. aromaticivorans induced signature antibodies against microbial PDC-E2 and its mitochondrial counterpart but also triggered chronic T cell-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
225
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(237 citation statements)
references
References 66 publications
7
225
1
4
Order By: Relevance
“…These effects require the presence of iNKT cells, CD1d expression by B cells, and the provision of CD40-CD40L signaling, CD80-CD86 costimulation, and IFN-γ, but not of . Formulations involving proteins such as hen egg lysozyme in complex with αGalCer, or haptenated-αGalCer molecules, cannot generate MHC-II-restricted epitopes, and this observation confirms the fact that cognate iNKT-cell-mediated B-cell help can elicit Ab production and class switch independently of Th-cell recruitment [50,51].Cognate iNKT-cell-mediated B-cell help has also been described to occur spontaneously in a model of infection with the hepatotropic sphingomonas Novosphingobium aromaticivorans, which contains glycosphingolipid analogs (α-glycurunilceramides) that activate iNKT cells and the B-cell Ag enzyme pyruvate dehydrogenases complex E2 [52]. Infection of mice with this bacterium elicits rapid iNKT-cell-dependent production of high-affinity and classswitched Abs against bacterial pyruvate dehydrogenases complex E2, which also cross-react with the homologous mammalian mitochondrial enzyme that is expressed in small bile ducts, thereby initiating organ damage that resembles human primary biliary cirrhosis [52].…”
supporting
confidence: 58%
See 1 more Smart Citation
“…These effects require the presence of iNKT cells, CD1d expression by B cells, and the provision of CD40-CD40L signaling, CD80-CD86 costimulation, and IFN-γ, but not of . Formulations involving proteins such as hen egg lysozyme in complex with αGalCer, or haptenated-αGalCer molecules, cannot generate MHC-II-restricted epitopes, and this observation confirms the fact that cognate iNKT-cell-mediated B-cell help can elicit Ab production and class switch independently of Th-cell recruitment [50,51].Cognate iNKT-cell-mediated B-cell help has also been described to occur spontaneously in a model of infection with the hepatotropic sphingomonas Novosphingobium aromaticivorans, which contains glycosphingolipid analogs (α-glycurunilceramides) that activate iNKT cells and the B-cell Ag enzyme pyruvate dehydrogenases complex E2 [52]. Infection of mice with this bacterium elicits rapid iNKT-cell-dependent production of high-affinity and classswitched Abs against bacterial pyruvate dehydrogenases complex E2, which also cross-react with the homologous mammalian mitochondrial enzyme that is expressed in small bile ducts, thereby initiating organ damage that resembles human primary biliary cirrhosis [52].…”
supporting
confidence: 58%
“…These studies used complex or particulated immunogens composed of proteins or hapten Ags that are either physically associated to αGalCer [50,51] or entrapped in bacterial fragments together with glycolipid analogs [52] (Fig. 1D and F).…”
Section: Cognate Help By Inkt Cellsmentioning
confidence: 99%
“…42 Most recently, Mattner et al supported the pathogenic role of N. aromaticivorans being able to induce serum autoantibodies and PBC-like liver lesions in mice following immunization. 43 A novel human beta-retrovirus has been recently reported in perihepatic lymph nodes and other samples from patients with PBC, thus Experimental evidence on immunopathogenesis of PBC C Selmi et al 3…”
Section: Environmental Factorsmentioning
confidence: 99%
“…This is particularly intriguing considering the previously mentioned study by Mattner et al, who demonstrated that in a murine model of PBC, N. aromaticivorans was capable of inducing autoreactive AMAs and chronic T-cellmediated autoimmunity against small bile ducts in an NKT-dependent fashion. 43 Animal models Similar to all complex diseases, such as autoimmune disease, the development of an animal model is of obvious importance in elucidating the mechanism(s) responsible for the initiation and progression of disease.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Previous studies by Mattner and colleagues have highlighted the role of bacterial infection in the pathophysiology of PBC [21]. Infection with Novosphinbium aromaticivorans promotes this autoimmune disease through invariant natural killer T cells …”
mentioning
confidence: 99%